Artifactual Hypoglycaemia in Systemic Sclerosis and Raynaud’s Phenomenon: A Clinical Case Report and Short Review - RH Bishay; A. Suryawanshi (Case Reports in Endocrinology)
Background. Artifactual hypoglycaemia, defined as a discrepancy between glucometer (capillary) and plasma glucose levels, may lead to overtreatment and costly investigations. It is not infrequently observed in patients with Raynaud’s phenomenon due to vascular capillary distortion, yet this is clinically underappreciated. Case Report. We report a 76-year-old woman with systemic sclerosis and Raynaud’s phenomenon, who presented with upper gastrointestinal bleeding and found to have concomitant persistent hypoglycaemia (1.0–2.7mmol/L) on a point-of-care glucometer in the absence hypoglycaemic symptoms. She underwent a 2-week hospital admission, repeated glucose monitoring, hydrocortisone replacement and dextrose infusions, with consequent hyperglycaemia on plasma measurements. Clinically, she did not satisfy Whipple’s triad and radiological investigations failed to identify pituitary or pancreatic pathology. A 72-hour fast was negative for hyperinsulinaemia or exogenous insulin use and her sulphonylurea metabolite urinary screen was negative. Discussion. Treatment of low capillary blood glucose is usually met with clinical impetus to treat, even when hypoglycaemic symptoms are lacking. The correct diagnosis may have been achieved had there been an observation of her cold hands, scleroderma facies, and consideration of the likely distorted peripheral microvasculature. Early identification of this presumably rare clinical scenario may have prevented overtreatment, altered methods of monitoring, and avoided unnecessary investigations.